The Development of HOTS-Oriented Science Supplement Book to Improve Problem Solving Ability of Vocational School Students - Farida, Camellia Green; Hartono, Hartono; Ridlo, Saiful (Journal of Innovative Science Education, 2021)
The 21st century is an era where information and knowledge technology developed rapidly. They are really affect all aspect of life especially on education sector. HOTS is one of the skills needed to face the challenges of the 21st century that requires students to think critically, creatively, and analyze an information which can be used as a way to solve the problem. This study aims to develop HOTS-oriented supplement books and find out the effectiveness of supplement books to improve students' problem-solving abilities. The supplement book that developed has HOTS characteristics which able to provoke students to improve their ability of reason, analyze, think creatively and solve the problems. This study uses a modified Research and Development (R&D) method. The results of this study 1) HOTS-oriented supplement book on polymer material in content / material and language in valid criteria according the experts with average of 3.78. Whereas in the graphic component, the language eligibility and the physical component of the supplement book is very valid criteria according to media experts 3,78. 2) The supplement book has oriented on HOTS polymer material developed which improves students' problem solving abilities effectively. It is proven by an increasing of post-test scores, with medium N-Gain criteria and achieve 100% classical completeness.